Study on self-similar call admission control algorithm in WiM AX - Yong-dong HU; Guo-xin WU; Ning QIAN; San-feng ZHANG (Tongxin xuebao)
As to the self-similarity of WiMAX network traffic,M/Pareto model was proposed to model network traf-fic.Through the statistical nature between the M/Pareto model and FBM traffic model,the parameters of the M/Pareto were mapped to the ones of FBM traffic model.The effective bandwidth formula was derived for M/Pareto model para-meters.Whereby,a self-similar call admission control algorithm(SS-CAC)was designed.It avoided getting the parame-ter values of FBM traffic flow model with the measurem method and adapted to the self-similarity of WiMAX traffic.Since the calculation of the effective bandwidth was accurate and convenient,simulation results show that SS-CAC greatly reduces the call blocking rate and improves the bandwidth utilization.